EFFECT OF FERMENTATION DURATION ON CAFEIN CURRENCY IN ROBUSTA COFFEE (Coffea canephora) FROM PTPN XII JEMBER - Rizka Handayani (Indonesian Pharmacopeia Journal, 2024)
Background: Indonesia is one of the largest coffee producing and exporting countries in the world. Jember Regency is one of the areas that develop robusta coffee, especially PT. Perkebunan Nusantara XII in the city of Jember has a coffee plantation area of 10,715 Ha. Coffee contains caffeine compounds. Caffeine is a xanthine alkaloid compound where most people believe that caffeine contained in coffee functions against drowsiness and fatigue. The fermentation process of coffee beans is a process in which the decomposition of complex compounds present in coffee beans, into simple compounds by adding some microorganisms to help release the mucus layer that still covers the coffee beans. BAL is a bacteria that can reduce the caffeine content in coffee. Methods: This research design is true experimental with UV-Vis Spectrophotometry method to determine the caffeine content. The sample used was robusta coffee beans (Coffea canephora) from PTPN XII Jember. Robusta coffee was fermented for 8, 18, 24 hours. Absorbance measurement was performed at a wavelength of 273 nm. Result : Caffeine levels in Robusta coffee that underwent BAL (Lactobacillus plantarum) fermentation process decreased due to the activity of proteolytic acid bacteria that produce protaseae enzymes high enough to cause caffeine levels in coffee to decrease. The results of caffeine levels can be seen in non-fermentation of 0,5212 mg/g, and 8 hours of fermentation time of 0,4437 mg/g, 18 hours of 0,3340 mg/g, and 24 hours of 0,1183 mg/g. Conclusion: The longer the fermentation time, the lower the caffeine content.